Targeting Tumor-Associated Macrophages as a Potential Strategy to Enhance the Response to Immune Checkpoint Inhibitors - Cassetta, Luca; Kitamura, Takanori (Frontiers in Cell and Developmental Biology, 2018)
Inhibition of immune checkpoint pathways in CD8+ T cell is a promising therapeutic strategy for the treatment of solid tumors that has shown significant anti-tumor effects and is now approved by the FDA to treat patients with melanoma and lung cancer. However the response to this therapy is limited to a certain fraction of patients and tumor types, for reasons still unknown. To ensure success of this treatment, CD8+ T cells, the main target of the checkpoint inhibitors, should exert full cytotoxicity against tumor cells. However recent studies show that tumor-associated macrophages (TAM) can impede this process by different mechanisms. In this mini-review we will summarize recent studies showing the effect of TAM targeting on immune checkpoint inhibitors efficacy. We will also discuss on the limitations of the current strategies as well on the future scientific challenges for the progress of the tumor immunology field.